POTENSI ANTIBAKTERI EKSTRAK ETANOL MENIRAN (Phyllanthus niruri L.) TERHADAP BAKTERI Streptococcus sobrinus DAN Salmonella typhi - Rakasiwi, Dea; Astuti, Winni; Marliana, Eva (JURNAL ATOMIK, 2023)
Meniran (Phyllanthus niruri L.) is one of the herb plants used as traditional medicine, such as toothache medicine and diarrhea medicine. The purposed of this study was to determined the type of secondary metabolites in the ethanol extract of meniran herb and to determined the minimum inhibitory concentration (MIC) value of the ethanol extract of meniran (Phyllanthus niruri L.) to Streptococcus sobrinus KCCM 11898 and Salmonella typhi ATCC 422. The ethanol extract of meniran was tested for phytochemicals. The MIC value of the ethanol extract of meniran herb for the test bacteria was obtained by varying the concentration of the ethanol extract of meniran herbs. Phytochemical test results showed that the ethanol extract of meniran herbs contains alkaloids, phenolics and steroids. The minimum inhibitory concentration value of the ethanol extract of meniran herb at the bacteria Streptococcus sobrinus KCCM 11898 and Salmonella typhi ATCC 422 each was 0.625%. Keywords: Phyllanthus niruri L, minimum inhibitory concentration (MIC), Streptococcus sobrinus KCCM 11898, Salmonella typhi ATCC 422